Analisis UU TPKS dan Fikih Mubadalah dalam Pembelajaran Fikih Pernikahan di Madrasah Aliyah - Latifah Latifah (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2024)
The paradoxical phenomenon of domestic violence (KDRT) within the ideal construct of Islamic marriage, supported by the prevalence of violence against women in Indonesia, forms the empirical basis of this research. Fikih mubadalah, as an interpretative framework that emphasizes the principle of reciprocity in understanding religious texts, and the Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS), as a juridical instrument providing comprehensive protection for victims of sexual violence, constitute the central conceptual elements of this study. This research focuses on the analysis of the implementation of UU TPKS and the fikih mubadalah paradigm within the pedagogical context of the Islamic Marriage Jurisprudence subject in the eleventh grade of Social Sciences at Madrasah Aliyah Negeri (MAN) 1 Banjarmasin. The research method employed is descriptive qualitative, with data collection techniques including participatory observation, semi-structured interviews with students and educators, and documentary analysis of learning artifacts. The research findings indicate that the integration of the fikih mubadalah concept and the substance of UU TPKS in the learning process significantly enhances students' understanding of the essence of egalitarian marital relations and the urgency of legal protection against gender-based violence. Students are able to identify manifestations of gender inequality in marriage case studies and internalize the importance of equality and legal protection guarantees. Nevertheless, heterogeneity in the level of understanding is still identified in a small portion of the sample population. The conclusion of this research is that the internalization of fikih mubadalah and UU TPKS within the Islamic Marriage Jurisprudence curriculum effectively stimulates students' critical awareness of the importance of just marital relations and the imperative of preventing acts of violence. The application of a contextual and participatory pedagogical approach proves to be positively correlated with an increase in students' understanding. This research recommends the adoption of a similar integrative approach in the religious education curriculum as a strategic effort to shape a young generation that possesses legal awareness, a fair gender perspective, and the capacity to build harmonious and violence-free family institutions.